Social welfare versus inequality concerns in an incomplete contract experiment - Marco Faravelli; Oliver Kirchkamp; Helmut Rainer (Center for Economic Studies and ifo Institute (CESifo), 2010)
We study a situation where two players first choose a sharing rule, then invest into a joint production process, and then split joint benefits. We investigate how social preferences determine investments. In our experiment we find that even the materially disadvantaged player cares more for social welfare than about inequality. Behavioral preferences of disadvantaged players actually increase inequality. We also investigate when players give up an advantageous sharing rule. Power-sharing can be successful in the experiment, even when it is not in a selfish world.
Keywords: C91; D23; D86; 330; experiments; incomplete contracts; relationship-specific investment; allocation of power; social preferences; Soziale Beziehungen; Soziale Ungleichheit; Gerechtigkeit; Soziale Wohlfahrtsfunktion; Unvollständiger Vertrag; Macht; Test